Development of Problem-Based Teaching Materials on the Role of Economic Actors to Foster Students' Critical Thinking in Madrasah Aliyah - Irmawati, Irmawati; Iswatiningsih, Daroe; Inganah, Siti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to develop problem-based teaching materials on the role of economic actors to improve the critical thinking skills of 10th-grade students at MA Muhammadiyah Balassuka, Gowa Regency. The study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research population consisted of all tenth-grade students, while the sample consisted of 27 students selected purposively, along with an economics teacher as a feasibility test respondent. Data sources included the results of validation by subject matter experts and language experts, observation of the learning process, and teacher and student response questionnaires. Data collection techniques included validation sheets, questionnaires, and documentation. The data were analyzed using quantitative and qualitative approaches. Quantitative analysis was performed to calculate the validity and response percentages using the criteria of very good (80–100%), good (60–79%), fair (40–59%), and poor (<40%). Qualitative analysis was used to interpret validator input, observation results, and respondent responses. The results showed that subject matter experts obtained a score of 90.5% and language experts obtained a score of 93.75%, which is considered highly valid. Teacher feasibility tests reached 92.3%, while student responses showed an effectiveness of 97.7%. Implementation of the module showed an increase in students' critical thinking skills through active discussion, the ability to construct arguments, and evaluate economic solutions. Thus, this problem-based module is declared feasible and effective for use as an alternative economic teaching material that encourages active learning and the development of higher-order thinking skills.